Storytelling in Miniature: Microfiction and Reader Participation (ENTHYMEMA, 2017)
This article proposes that Iser’s work on gaps and blanks, as well as recent enactivist-inspired cognitive-narratological extensions of Iser’s work, can enlighten an under-theorized genre of experimental narrative, microfiction, typically identified as stories under 300 words (though often considerably shorter). The extreme brevity of microfiction results in stories that are similar, to a degree, to short stories, though experientially quite different; in the most thorough narratological treatment, William Nelles (2012) makes the case for a generic distinction between microfiction and the traditional short story. As I have argued elsewhere (Author 2016), borderline-narrative texts (microfiction included) make for oddly compelling reading experiences, largely due to the increased degree of reader participation necessary in narrativization. A main point of investigation here is as follows: while there is general agreement that Iser at least somewhat underestimates the extent to which narratives are perpetually fraught with gaps to be filled in by readers, there is still arguably a noticeably greater gap-per-capita (in a manner of speaking) in microfiction set against higher-narrativity texts; readers need to do more, in other words, to narrativize the typical piece of microfiction. Further, the extreme brevity of microfiction potentially affords readers a uniquely full experience of perceptual presence over the course of the micro-story.
Keywords: microfiction; experimental narrative; cognitive narratology; reader participation